2015
DOI: 10.1186/s12885-015-1047-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes type II and chronic inflammation on pancreatic cancer

Abstract: BackgroundWe explored if known risk factors for pancreatic cancer such as type II diabetes and chronic inflammation, influence the pathophysiology of an established primary tumor in the pancreas and if administration of metformin has an impact on tumor growth.MethodsPancreatic carcinomas were assessed in a syngeneic orthotopic pancreas adenocarcinoma model after injection of 6606PDA cells in the pancreas head of either B6.V-Lepob/ob mice exhibiting a type II diabetes-like syndrome or normoglycemic mice. Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
(55 reference statements)
2
23
0
Order By: Relevance
“…The latter finding is in line with previous studies [2] and could be caused by lower testosterone levels in diabetic men [23,24]. There is evidence to support diabetes as a genuine risk factor in the pathogenesis of liver and pancreatic cancers beyond the complex interplay of different risk factors, detection bias, cancer treatment and the effects of reverse causality as these cancers can also impair glucose metabolism [25][26][27][28][29][30]. In a metaanalysis, a twofold higher risk of hepatocellular carcinoma was seen in diabetic compared to nondiabetic subjects, with potential mechanisms including inflammation, cellular proliferation stimulated by hyperinsulinemia, high IGF-1 levels, and We found significantly increased cancer risks for sulfonylureas and decreased risks for oral glucose-lowering drugs, glitazones, simvastatin, pravastatin, fluvastatin, atorvastatin and rosuvastatin for female and male patients, as well as decreased risks for metformin in men.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The latter finding is in line with previous studies [2] and could be caused by lower testosterone levels in diabetic men [23,24]. There is evidence to support diabetes as a genuine risk factor in the pathogenesis of liver and pancreatic cancers beyond the complex interplay of different risk factors, detection bias, cancer treatment and the effects of reverse causality as these cancers can also impair glucose metabolism [25][26][27][28][29][30]. In a metaanalysis, a twofold higher risk of hepatocellular carcinoma was seen in diabetic compared to nondiabetic subjects, with potential mechanisms including inflammation, cellular proliferation stimulated by hyperinsulinemia, high IGF-1 levels, and We found significantly increased cancer risks for sulfonylureas and decreased risks for oral glucose-lowering drugs, glitazones, simvastatin, pravastatin, fluvastatin, atorvastatin and rosuvastatin for female and male patients, as well as decreased risks for metformin in men.…”
Section: Discussionsupporting
confidence: 89%
“…In a meta‐analysis, a twofold higher risk of hepatocellular carcinoma was seen in diabetic compared to nondiabetic subjects, with potential mechanisms including inflammation, cellular proliferation stimulated by hyperinsulinemia, high IGF‐1 levels, and hyperglycaemia favouring development of steatosis and cirrhosis . Pancreatic cancer was also reported to be more common in diabetic subjects in whom it was suspected that hyperglycaemia may be the major mechanistic driver for this interrelation . Indeed, a dose–response meta‐analysis revealed that every 0.56 mmol L −1 increase in fasting glucose was associated with a 14% increase in the rate of pancreatic cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such agent, currently under intense clinical investigation, is metformin, the most widely prescribed anti-diabetic generic drug that is also frequently administered to diabetic PDAC patients [47]. Metformin can improve treatment outcomes in preclinical models of cancer, particularly in the obese setting [1,3,58,86,112,118,127,152,164,170,178,181]. In addition, it reduces the incidence of cancer in diabetic patients as well as improves survival in newly diagnosed cases [28,94,97,102,144,152].…”
Section: Potential New Links Between Obesity and Cancer: Obesity Is Amentioning
confidence: 99%
“…Studies designed to unravel the mechanistic link between DM and PaC are complicated by the fact that type 2 DM, the most common form of DM, could promote PaC through a variety of factors, including hyperglycaemia itself, dyslipidaemia, chronic inflammation, and insulin resistance/hyperinsulinaemia . Recently, a tumour‐promoting role has been suggested for receptor for advanced glycation end‐products (RAGE), a single transmembrane receptor of the immunoglobulin superfamily.…”
Section: Introductionmentioning
confidence: 99%